2017
DOI: 10.18488/journal.63.2017.53.50.54
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of Zrtio4 Thin Films Prepared by Reactive Magnetron Co-Sputtering Without Heating

Abstract: Article HistoryZrTiO4 thin films were deposited by reactive dc magnetron co-sputtering method without heating. The crystal structure, surface morphology, thickness, optical and dielectric properties of the thin films were investigated. At sputtering currents above 2.0 A without heating ZrTiO4 thin film was crystallization of the orthorhombic phase (111). The values of refractive index were ranged between 2.01 and 2.23 (at 650 nm). The optical packing density values were ranged between 0.85 and 0.96. From this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…1a shows the XRD pattern of the ZrTiO 4 thin films deposited on Si (100) wafers at different sputtering currents of 0.5 and 1.5 A, which exhibits an orthorhombic crystal structure (JCPDS 34-0415) and possesses-PbO 2 -type structure belonging to the Pbcn space group. The ZrTiO 4 thin films were amorphous structureat sputtering currents of 0.5 A and 1.5 A without heating [8] and show preferred orientation in (111) direction at sputtering currents of 1.5 A with heat 600 °C. The other observed XRD patterns are (011), (020), (200), (120), (201), (121), (211), (220), (022), (202), (122), (311), (222) and (320) peaks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1a shows the XRD pattern of the ZrTiO 4 thin films deposited on Si (100) wafers at different sputtering currents of 0.5 and 1.5 A, which exhibits an orthorhombic crystal structure (JCPDS 34-0415) and possesses-PbO 2 -type structure belonging to the Pbcn space group. The ZrTiO 4 thin films were amorphous structureat sputtering currents of 0.5 A and 1.5 A without heating [8] and show preferred orientation in (111) direction at sputtering currents of 1.5 A with heat 600 °C. The other observed XRD patterns are (011), (020), (200), (120), (201), (121), (211), (220), (022), (202), (122), (311), (222) and (320) peaks.…”
Section: Methodsmentioning
confidence: 99%
“…Table 2 shows the dielectric properties of the ZrTiO 4 thin films at different sputtering currents of 0.5 and 1.5 A. And 1 MHz dielectric properties of ZrTiO 4 thin films at sputtering currents, it is observed that as the sputtering current increases, the high dielectric constant width decreases from 74.3 to 52.1 for ZrTiO 4 thin films without heating [8] which are higher more than which had researched because of higher energy. Moreover ZrTiO 4 thin films with heat 600 °C are valuable high dielectric constant has increased to 129.2 [7].…”
Section: Cross-sectional Morphologymentioning
confidence: 96%